The university that was, that is and that there may be in the future university education in Brazil - Estanislau , J. Félix (Seven Editora, 2023)
The formation of the university in Brazil was a consequence of the need for modernization of the growing Brazilian civilization engendered by the growing Western Greek Scientific Renaissance and its Revolutions and Capitalism opposites to the principles of Mercantilism and Monarchy, which had expanded and taken ascension in Europe, in North America and its colonies. But then what is the university that existed and exists in Brazilian territory? And, what future university could there be in Brazil? To answer these questions two methodological criteria were adopted: the study of recent bibliographic sources and the critical, analytical and relational capabilities of the true and current facts under study in this article. DOI:https://doi.org/10.56238/sevened2023.006-029